Efficacy of fenbendazole against gastrointestinal nematodes in naturally infected goats in Maputo Province, Mozambique using in vivo, in vitro and molecular assessment - Edna F.X. Guinda; Sonia M.S. Afonso; Stefan Fiedler; Eric R. Morgan; Sabrina Ramünke; Marc Borchert; Alsácia Atanásio; Bettencourt P.S. Capece; Jürgen Krücken; Georg von Samson-Himmelstjerna (International Journal for Parasitology: Drugs and Drug Resistance)
Anthelmintic resistance occurs worldwide in strongyles of ruminants but data from low-income countries are sparse and rarely apply most up to date methods, while effects of management practices in these countries are poorly documented. In Mozambique, benzimidazole resistance has been previously reported; the present study followed this up in detail, applying in vivo faecal egg count (FEC) reduction test (FECRT), in vitro egg hatch test (EHT) and molecular deep amplicon sequencing approaches targeting the internal transcribed spacer 2 (ITS-2, nemabiome) and the isotype 1 β-tubulin gene to determine the resistance status on farms and the strongyle species involved. Adult Landim goats (433) from six semi-intensive and ten extensive farms (22–30 animals/farm) from Maputo Province were visited April 2021 to February 2022. Fenbendazole (5 mg/kg bw, Panacur®) was administered orally and FEC determined using Mini-FLOTAC. The eggCounts package was used to calculate FECRs with 90% confidence intervals from paired day 0 and 14 data. In vivo and in vitro tests detected AR on 5/16 (31%) farms. This included 1/10 extensive and 4/6 semi-intensive farms. The odds of finding resistant strongyles on a semi-intensive commercial farm was 40-fold higher than on an extensive farm (p = 0.016, logistic regression). A strong, negative correlation was observed between FECRT and EHT EC50 values (Pearson's R = −0.83, P = 0.001; Cohen's κ coefficient 1.0). Nemabiome data showed that Haemonchus contortus, Trichostrongylus colubriformis and unclassified Oesophagostomum closely related to Oesophagostomum columbianum were most abundant before treatment and in particular H. contortus frequencies increased after treatment. Benzimidazole resistance associated polymorphisms were detected in H. contortus and T. colubriformis. Moreover, there were hints that resistance alleles were present in Trichostrongylus axei and Teladorsagia circumcincta. Farmers should regularly test the efficacy of anthelmintics used and consider more sustainable worm control approaches to reduce selection for resistance.